Optimalisasi Budaya Kerja di PT PAL Indonesia: Studi Literatur Review - Saidati Nor Wildana,; Mochammad Isa Anshori, (Journal of Management and Creative Business, 2024)
Organizational culture has a significant role in shaping company performance and employee satisfaction. This study aims to conduct an in-depth review of the literature related to organizational culture and the literature review research method was chosen to present a comprehensive overview of this topic. The research method used is literature review, in which data is obtained from various literature sources such as academic journals, books, and other scientific publications. This approach makes it possible to identify patterns, trends, and important findings relating to organizational culture.